Gene Expression Analysis of a Porcine Native Abdominal Aortic Aneurysm Model - Sadek, Mikel (2008)
INTRODUCTION: This study sought to characterize the gene expression patterns occurring during the development of aneurysms in the native porcine aorta. METHODS: In Yorkshire swine, the infrarenal aorta was balloon-dilated and infused with a solution of Type I collagenase/pancreatic porcine elastase (16000Units/1000Units). Aneurysmal and control aortic samples were obtained at one(N=3), two(N=6) and four(N=5) weeks following aneurysm induction. RNA was isolated, converted to biotin-modified antisense RNA and hybridized to porcine genome arrays. Aneurysmal and control gene intensities were compared using the two-sample-for-means z-test. P<0.01 was considered statistically significant. RESULTS: Extracellular matrix remodeling genes that were up-regulated in aneurysmal compared to control tissue included matrix metalloproteinase-1,-2,-3,-9 and MT-MMP, cathepsin-D,-H,-K,-S, TIMP-1 and collagen I-α1 chain (P<0.01). Elastin exhibited temporally down-regulated gene expression (P<0.01). Inflammatory genes that were up-regulated included ICAM-2, TNF-α, Il-1β, Il-10, CXCR-4 and tPA (P<0.01). Atherosclerosis and cancer genes that were up-regulated included apoE, acyl-CoA binding protein, FLI-1 and ETS (P<0.01). CONCLUSION: The porcine model replicates the gene expression patterns that are observed during the development of aneurysms in human studies as well as in rodent models. The porcine model thereby represents a novel method to study the impact of endovascular, cell-based and other therapeutic interventions on AAA pathophysiology.